Household willingness to pay for azithromycin treatment for trachoma control in the United Republic of Tanzania - Frick Kevin D.; Lynch Matthew; West Sheila; Munoz Beatriz; Mkocha Harran A. (The World Health Organization, 2003)
OBJECTIVE: Household willingness to pay for treatment provides important information for programme planning. We tested for relationships between socioeconomic status, risk of trachoma, perceptions of the effects of azithromycin, and the household willingness to pay for future mass treatment with azithromycin. METHODS: We surveyed 394 households in 6 villages located in central United Republic of Tanzania regarding their willingness to pay for future azithromycin treatment. A random sample of households with children under 8 years of age was selected and interviewed following an initial treatment programme in each village. Data were gathered on risk factors for trachoma, socioeconomic status, and the perceived effect of the initial azithromycin treatment. Ordered probit regression analysis was used to test for statistically significant relationships. FINDINGS: 38% of responding households stated that they would not be willing to pay anything for future azithromycin treatment, although they would be willing to participate in the treatment. A proxy for cash availability was positively associated with household willingness to pay for future antibiotic treatment. Cattle ownership (a risk factor) and being a household headed by a female not in a polygamous marriage (lower socioeconomic status) were associated with a lower willingness to pay for future treatment. A perceived benefit from the initial treatment was marginally associated with a willingness to pay a higher amount. CONCLUSIONS: As those at greatest risk of active trachoma indicated the lowest willingness to pay, imposing a cost recovery fee for azithromycin treatment would likely reduce coverage and could prevent control of the disease at the community level.